Filsafat Dan Pendidikan: Menemukan Pertalian Ilmu - Gregorius We’u (Ekspektasi: Jurnal Pendidikan Ekonomi, 2018)
Philosophy is the science of all sciences or the mother of all sciences. It means that philosophy is the source of all knowledge that exists. Philosophy be the sole cause existing development in the overall aspects of basic and not experienced by humans. Moreover, the philosophy is also a science that focuses on the study of the entire universe. Philosophy is a basic change in thinking and human thought. Education in Indonesia at present has experienced a rapid development, the success of the manusai Indonesia in general and students in particular. The process of development experienced by learners ushered in a successful life as a human. it appears in the objectives of the National Education System Law no. 20 in 2003. Thus it can be understood that the philosophy of education as a guide or foundation for Indonesia's education in order to develop the mandate of the Constitution of 1945 on Indonesian education. Therefore, the philosophy of education need to be studied in the realm of formal education. This is done as a form of learning on what needs to be the standard in the world of education.